Combining Controlled-Release and Normal Urea Enhances Rice Grain Quality and Starch Properties by Improving Carbohydrate Supply and Grain Filling - Chang Liu; Tianyang Zhou; Zhangyi Xue; Chenhua Wei; Kuanyu Zhu; Miao Ye; Weiyang Zhang; Hao Zhang; Lijun Liu; Zhiqin Wang; Junfei Gu; Jianchang Yang (Plants)
Controlled-release nitrogen fertilizers are gaining popularity in rice (Oryza stavia L.) cultivation for their ability to increase yields while reducing environmental impact. Grain filling is essential for both the yield and quality of rice. However, the impact of controlled-release nitrogen fertilizer on grain-filling characteristics, as well as the relationship between these characteristics and rice quality, remains unclear. This study aimed to identify key grain-filling characteristics influencing rice milling quality, appearance, cooking and eating qualities, and physicochemical properties of starch. In this study, a two-year field experiment was conducted that included four nitrogen management practices: zero nitrogen input (CK), a local high-yield practice with split urea applications (100% urea, CU), a single basal application of 100% controlled-release nitrogen fertilizer (CRNF), and a basal application blend of 70% controlled-release nitrogen fertilizer with 30% urea (CRNF-CU). The results showed that a sufficient amount of carbohydrates for the rice grain-filling process, as indicated by a higher sugar–spikelet ratio, is essential for improving grain quality. An increased sugar–spikelet ratio enhances the grain-filling process, resulting in an elevated average grain-filling rate (Gmean) and the peak grain-filling rate (Gmax), while also reducing the overall time required for grain filling (D). Compared to CU, CRNF and CRNF-CU treatments did not significantly change milling qualities, but reduced the chalky kernel rate and chalkiness, thereby enhancing the appearance quality. These treatments increased the amylose and amylopectin contents while reducing protein content, though the proportion of protein constituents remained unchanged. These treatments led to larger starch granules with notably smoother surfaces. Additionally, CRNF and CRNF-CU reduced relative crystallinity and structural order, while increasing the amorphous structure in the outer region of starch granules, which lowered rice starch crystal stability. The treatments also increased viscosity and improved the thermodynamic properties of starch, resulting in enhanced eating and cooking quality of the rice. In conclusion, the CRNF-CU is the most effective strategy in this study to enhance both grain yield and quality. This practice ensures an adequate carbohydrate supply for grain filling, which is essential for efficient grain filling and improved overall quality.